Saúde, comunicação e nanotecnologia: o papel do debate público para a expansão da cidadania - Resende, Letícia Passos; Rothberg, Danilo [UNESP] (My University, 2010)
Amongst thematic networks, strategic laboratories and master and doctorate scholarships awarded by the National Program of Nanotechnology, an actor of great relevance can be distinguished due to its relative absence: the lay people, once more relegated to a secondary agent in Brazilian democracy, although citizens’ views have been increasingly recognized all over the world as an indispensable factor to the science and technology public policies which are intended to be democratic. Whereas Europe and United States have incorporated public values and feelings in the policy planning, Brazil is still waiting for opportunities of public participation in the definition of research guidelines. This paper examines contemporaneous demands of science communication to the strengthening of citizenship, aiming to offer contributions to a debate directed to question the present arrangement — of antidemocratic indifference towards the public — adopted in the formulation of public policies in Brazil.

Entre redes temáticas, laboratórios estratégicos e bolsas de mestrado e doutorado fomentados pelo Programa Nacional de Nanotecnologia, destaca-se, por sua relativa ausência, um ator de grande relevância: o público leigo, mais uma vez relegado a agente secundário na democracia brasileira, embora as perspectivas dos cidadãos em geral sejam cada vez mais reconhecidas em todo o mundo como fator imprescindível à formulação de políticas de ciência e tecnologia que se pretendam democráticas. Enquanto Europa e Estados Unidos têm incorporado valores e sensibilidades do público no planejamento de políticas, no Brasil ainda são esperadas oportunidades de participação pública na definição de diretrizes de pesquisa. Este trabalho examina exigências contemporâneas da comunicação de ciência e tecnologia para o fortalecimento da cidadania, a fim de oferecer contribuições a um debate que se propõe a questionar o atual formato — de indiferença antidemocrática ao público — adotado na construção de políticas públicas do setor no Brasil.
Keywords: Nanotechnology; Health; Communication; Political participation; Citizenship; Nanotecnologia; Saúde; Comunicação; Participação política; Cidadania